Degradation of Phenol Using Sonolysis and Photolysis by TiO2/RHAC Catalyst and Analysis with Spectrophotometer UV-VIS and HPLC - Safni - Safni; Eno Okta Patricia; Trisna Ollinovela; Yulizar Yusuf (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
This study focuses on the degradation of phenol in aqueous solutions using photolysis and sonolysis methods. It investigates the impact of catalyst mass, types of light (UV-A, UV-C, and visible light), types of catalyst (RHAC, TiO2, and TiO2/RHAC), and processing time on phenol degradation. The phenol solutions are analyzed before and after degradation using Spectrophotometer UV-Vis and HPLC. The research aims to understand the factors influencing phenol degradation and provide a basis for further studies to enhance the efficiency of phenol removal. Results show significant improvements in degradation percentages of phenol by using TiO2/RHAC as the catalyst. Sonolysis achieves a degradation of 20.82% with a catalyst, which increases to 50.57% with the catalyst. Photolysis achieves a degradation of 29.06%, which rises to 91.99% with the catalyst. The highest degradation percentage is achieved using UV-A light for 5 hours with a catalyst mass of 30 mg of TiO2/RHAC catalyst. HPLC analysis confirms a decreased phenol concentration and the presence of intermediate compounds. The TiO2/RHAC catalyst demonstrates the promising potential for efficient phenol degradation in aqueous solutions.